The impact of maumere gymnastics on blood pressure reduction in hypertensive patients: A promising non-pharmacological intervention - Sari, Anggun Permata; Bafirman,; Rifki, Muhammad Sazeli; Syafrianto, Donal; Kurniawan, Randi (Journal Sport Area, 2023)
Hypertension is one of the biggest causes of morbidity in the world, often referred to as a silent killer. This study aimed to investigate the effectiveness of Maumere exercise, a non-pharmacological therapy, in reducing blood pressure among hypertensive individuals in Padang City. An experimental research design with a pretest-posttest approach was employed, involving 20 participants aged 25 years and older who had a history of stage 1 hypertension. Blood pressure measurements were obtained using a sphygmomanometer, and the data were analysed using t-tests or regression analysis. The findings demonstrated that Maumere exercise therapy effectively reduced systolic blood pressure by 43.5% and diastolic blood pressure by 48.7%. Additionally, Maumere gymnastic exercises were found to have a positive impact on heart rate control. Regular exercise led to improved cardiovascular adaptation, resulting in better blood pressure control. This study contributes by providing empirical evidence regarding the efficacy of Maumere exercise as a non-pharmacological therapy for reducing blood pressure in hypertensive patients. It highlights the significant reduction in systolic and diastolic blood pressure achieved through four weeks of Maumere gymnastics, supporting its potential as an alternative approach to hypertension management. Future research should consider larger-scale studies with diverse populations, explore the long-term effects of Maumere exercise, and investigate the optimal duration, frequency, and intensity of exercise sessions to develop standardised guidelines for its implementation.